-6x-5(-3x-3)=-84

Simple and best practice solution for -6x-5(-3x-3)=-84 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x-5(-3x-3)=-84 equation:


Simplifying
-6x + -5(-3x + -3) = -84

Reorder the terms:
-6x + -5(-3 + -3x) = -84
-6x + (-3 * -5 + -3x * -5) = -84
-6x + (15 + 15x) = -84

Reorder the terms:
15 + -6x + 15x = -84

Combine like terms: -6x + 15x = 9x
15 + 9x = -84

Solving
15 + 9x = -84

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15' to each side of the equation.
15 + -15 + 9x = -84 + -15

Combine like terms: 15 + -15 = 0
0 + 9x = -84 + -15
9x = -84 + -15

Combine like terms: -84 + -15 = -99
9x = -99

Divide each side by '9'.
x = -11

Simplifying
x = -11

See similar equations:

| 2-cosx=0 | | 11.98=5.75+0.89m | | 4r-4(4r+5)=-104 | | Y=-x-7x | | Y/215 | | w+48+43w+48+w+39=180 | | (4+5)-5=-5 | | 0.6(x+70)+0.6x=78 | | 8(4r-8)=38+2r | | 2x+100+100+75=450 | | X=-85+y | | (9x+15)(12x+21)=0 | | 36/3.14 | | 5.39-2.20= | | x^3-2.5*x^2-20=0 | | 12x^3+8x^2-15x-10=0 | | 8x-2y-3y^2=0 | | -3p+7=5-(20p+4) | | -p^2+50p=0 | | 3x(6+b)=30 | | 3n-12n=5 | | 2lnx+ln(x+1)= | | 19+(x-50)=90 | | 3/4m-6=5/8 | | 35=18x-13x | | 12x-(2x+5)=16 | | g+4g+1= g+8g+9 | | K=-10 | | 545=125+30x | | 5x+5-12=3x+36-6 | | 58.5=2/9.75x | | 10+(-5)+6=n |

Equations solver categories